ANALISIS HUKUM TERHADAP UPAYA PERLINDUNGAN DAN PEMBERDAYAAN NELAYAN KECIL DAN PEMBUDI DAYA IKAN - Mohammad Ismail Hairun (JURNAL AKTA YUDISIA, 2020)
Most fishermen and fish breeders live in poverty, are poorly educated and live in an atmosphere of business uncertainty. As part of citizens, they are constitutionally entitled to the protection and empowerment of the state. Therefore, the Republic of Indonesia Law No. 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers, and Salt Farmers was born. Two problem statements are raised, namely first; Legis ratio of protection and empowerment of fishermen, and secondly; a form of protection and empowerment of fishers and fish breedersThe research method used is a normative juridical research method because it uses primary and secondary legal materials with a qualitative analysis approach.Based on the results of the study can be concluded first; Legis ratio of protection and empowerment of fishermen and fish cultivators because fishermen and fish breeders are generally categorized as poor, low-educated, and powerless. As part of citizens who are entitled to fair legal recognition, guarantee, protection and certainty, and equal treatment before the law. Philosophically protect fishermen and fish breeders in conducting their business so that they are free or avoiding various problems and subsequently increase capacity in various aspects that benefit them.Both forms of protection for fishermen and fish farmers in the form of providing infrastructure and means of production of business activities, in the form of fishing gear, ships and/or ports, land and water ponds, and irrigation channels, provide guarantees of business certainty, guarantees of risk of catching and cultivating fish and elimination of high-cost economic practices. While the empowerment of fishermen and fish farmers is done by increasing the capacity of fishermen and fish farmers through education and training, fostering a spirit of self-sufficiency through counseling and mentoring, providing opportunities and opportunities for marketing, capital, increasing human resources, providing financing and capital facilities. Keywords; Protection, Empowerment, Fishermen and Fish breeders